FRA1 Kinesin Modulates the Lateral Stability of Cortical Microtubules through Cellulose Synthase–Microtubule Uncoupling Proteins. Issue 8 (2nd June 2020) - Ganguly, Anindya; Zhu, Chuanmei; Chen, Weizu; Dixit, Ram
Abstract : The FRA1 kinesin affects the positional stability of its tracks by regulating the levels of CMU proteins available to bind to cortical microtubules. Abstract: Cell wall assembly requires harmonized deposition of cellulose and matrix polysaccharides. Cortical microtubules orient the deposition of cellulose by guiding the trajectory of cellulose synthase complexes. Vesicles containing matrix polysaccharides are thought to be transported by the FRAGILE FIBER1 (FRA1) kinesin to facilitate their secretion along cortical microtubules. The cortical microtubule cytoskeleton thus may provide a platform to coordinate the delivery of cellulose and matrix polysaccharides, but the underlying molecular mechanisms remain unknown. Here, we show that the tail region of the Arabidopsis ( Arabidopsis thaliana ) FRA1 kinesin physically interacts with cellulose synthase–microtubule uncoupling (CMU) proteins that are important for the microtubule-dependent guidance of cellulose synthase complexes. Interaction with CMUs did not affect microtubule binding or motility of the FRA1 kinesin but differentially affected the protein levels and microtubule localization of CMU1 and CMU2, thus regulating the lateral stability of cortical microtubules. Phosphorylation of the FRA1 tail region inhibited binding to CMUs and consequently reversed the extent of cortical microtubule decoration by CMU1 and CMU2. Genetic experiments demonstrated the significance of this interaction to the growth and reproduction of Arabidopsis plants. We propose that modulation of CMU protein levels and microtubule localization by FRA1 provides a mechanism that stabilizes the sites of deposition of both cellulose and matrix polysaccharides.